2022
DOI: 10.3389/fped.2022.819998
|View full text |Cite
|
Sign up to set email alerts
|

The Global Prevalence of Amblyopia in Children: A Systematic Review and Meta-Analysis

Abstract: Epidemiological data about the prevalence of amblyopia around the world vary widely among regions and periods. This meta-analysis aimed to determine the global prevalence of amblyopia in children. PubMed, Embase, and the Cochrane Library were searched for prevalence studies published up to 5 November 2021. The outcome was the prevalence of amblyopia, analyzed as pooled estimates with 95% confidence intervals (CI). A total of 97 studies were included, including 4,645,274 children and 7,706 patients with amblyop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 108 publications
0
23
1
Order By: Relevance
“…Amblyopia is a neurological disorder that affects the development of the visual system in early life [ 1 , 2 , 3 ]. Several studies have reported and listed the differences that are present between strabismic and anisometropic amblyopia [ 4 , 5 ], this differential behavior being an important factor when considering the protocol for amblyopia rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Amblyopia is a neurological disorder that affects the development of the visual system in early life [ 1 , 2 , 3 ]. Several studies have reported and listed the differences that are present between strabismic and anisometropic amblyopia [ 4 , 5 ], this differential behavior being an important factor when considering the protocol for amblyopia rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Amblyopia was present in 1.36% of people worldwide being generally of 95% CI: 1.27-1.46%. Males were more likely to experience amblyopia (OR = 0.885, 95% CI: 0.795-0.985, P = 0.025) than females (1.24%, 95% CI: 0.94-1.54%), our results slightly differing in gender distribution [ 10 ].…”
Section: Discussionmentioning
confidence: 84%
“…The prevalence of amblyopia worldwide varies widely among regions and periods. Early diagnosis and treatment help restore vision [2, 3]. Amblyopia results from a cortical visual imbalance, but retinal level changes may also be present [1, 4].…”
Section: Introductionmentioning
confidence: 99%